The relationship between chlorophyllous spores and mycorrhizal associations in ferns: evidence from an evolutionary approach. Issue 12 (8th December 2022) - Mellado‐Mansilla, Daniela; Testo, Weston; Sundue, Michael A.; Zotz, Gerhard; Kreft, Holger; Coiro, Mario; Kessler, Michael
Abstract: Premise: Approximately 14% of all fern species have physiologically active chlorophyllous spores that are much more short‐lived than the more common and dormant achlorophyllous spores. Most chlorophyllous‐spored species (70%) are epiphytes and account for almost 37% of all epiphytic ferns. Chlorophyllous‐spored ferns are also overrepresented among fern species in habitats with waterlogged soils, of which nearly 60% have chlorophyllous spores. Ferns in these disparate habitat types also have a low incidence of mycorrhizal associations. We therefore hypothesized that autotrophic chlorophyllous spores represent an adaptation of ferns to habitats with scarce mycorrhizal associations. Methods: We evaluated the coevolution of chlorophyllous spores and mycorrhizal associations in ferns and their relation to habitat type using phylogenetic comparative methods. Results: Although we did not find support for the coevolution of spore type and mycorrhizal associations, we did find that chlorophyllous spores and the absence of mycorrhizal associations have coevolved with epiphytic and waterlogged habitats. Transition rates to epiphytic and waterlogged habitats were significantly higher in species with chlorophyllous spores compared to achlorophyllous lineages. Conclusions: Spore type and mycorrhizal associations appear to play important roles in the radiation of ferns into different habitat types. Future work should focus on clarifying the functional significance of these associations.